Snowfall Fraction, Cold Content, and Energy Balance Changes Drive Differential Response to Simulated Warming in an Alpine and Subalpine Snowpack - Jennings, Keith S.; Molotch, Noah P. (Frontiers in Earth Science, 2020)
Despite widespread warming in mountain regions, little research to date has explored the physical mechanisms driving the variable response of snowpacks to changes in climate, instead focusing primarily on empirical relationships, such as seasonal air temperature or elevation. In this work, we evaluate how differences in snowfall fraction, cold content, and the snowpack energy balance produce simulated changes to snow accumulation and melt at an alpine and subalpine snowpack in the Niwot Ridge Long Term Ecological Research site. For our analysis, we created a 23 years baseline simulation using the SNOWPACK model forced by historical hourly meteorological data from water year 1991 through 2013. We then perturbed hourly air temperature in 0.5°C increments from +0.5 to +4.0°C above baseline and increased incoming longwave radiation accordingly. For every 1°C of warming, peak snow water equivalent declined by 43.9 mm in the alpine and 54.3 mm in the subalpine, melt onset shifted 6.2 days earlier in the alpine and 8.8 days in the subalpine, the snow season shortened by 10.7 days in the alpine and 16.4 days in the subalpine, and melt rate increased by 0.2 mm d−1 in the alpine while decreasing by 0.4 mm d−1 in the subalpine. We found the alpine snowpack was less sensitive to warming for three primary reasons: (1) Snowfall fraction decreased less rapidly per 1°C of warming than in the subalpine; (2) Cold content still consistently developed throughout the snow season, preventing mid-winter melt events; (3) Changes to snowmelt rate were not significant because increases to the turbulent fluxes balanced decreases in the radiative fluxes with earlier snowmelt onset. Additionally, at 3°C of warming and greater, the subalpine site experienced a fundamental shift where significant melt could occur throughout the entirety of the winter as cold content was no longer large enough to buffer against positive energy fluxes. In some years, the subalpine snowpack became transient with several cycles of accumulation and melt per winter. This tipping point suggests sites with lower cold content—like the subalpine studied here—are likely to be more sensitive to producing increased winter melt as warming continues over the coming decades.